Linalool oxide: generalist plant based lure for mosquito disease vectors. Issue 1 (December 2015) - Nyasembe, Vincent; Tchouassi, David; Mbogo, Charles; Sole, Catherine; Pirk, Christian; Torto, Baldwyn
Abstract Background Lack of effective vaccines and therapeutics for important arboviral diseases such as Rift Valley fever (RVF) and dengue, necessitates continuous monitoring of vector populations for infections in them. Plant-based lures as surveillance tools has the potential of targeting mosquitoes of both sexes and females of varied physiological states; yet such lures are lacking for vectors of these diseases. Here, we present evidence of the effectiveness of linalool oxide (LO), a single plant-based lure previously developed for malaria vectors in trapping RVF vectors, Aedes mcintoshi andAedes ochraceus, and dengue vector, Aedes aegypti . Methods For RVF vectors, we used CDC traps to evaluate the performance of LO against three vertebrate-based lures: CO2 (dry ice), BioGent (BG) lure, and HONAD (a blend of aldehydes) in 2 experiments with Completely Randomized design: 1) using unlit CDC traps baited separately with LO, HONAD and BG-lure, and unlit CDC trap + CO2 and lit CDC trap as controls, 2) similar treatments but with inclusion of CO2 to all the traps. For dengue vectors, LO was evaluated against BG lure using BG sentinel traps, in a 3 × 6 Latin Square design, first as single lures and then combined with CO2 and traps baited with CO2 included as controls. Trap captures were compared between the treatments using Chi square and GLM. Results Low captures of RVF vectors were recorded for all lures in the absence of CO2 with no significant difference between them. When combined with CO2, LO performance in trapping these vectors was comparable to BG-lure and HONAD but it was less effective than the lit CDC trap. In the absence of CO2, LO performed comparably with the BG-lure in trapping femaleAe. aegypti, but with significantly higher males recorded in traps baited with the plant-based lure. When CO2 was added, LO was significantly better than the BG-lure with a 2.8- fold increase in captures of maleAe. aegypti . Conclusions These results highlight the potential of LO as a generalist plant-based lure for mosquito disease vectors, pending further assessment of possible specificity in their response profile to the different stereoisomers of this compound.